First Records of Odonata (Insecta) From the Bodoquena Mountains, Mato Grosso do Sul, Brazil - Dalzochio, Marina Schmidt; de Souza, Luiz Onofre Irineu; Uchoa, Manoel Araécio; Costa, Janira Martins (EntomoBrasilis, 2011)
In this study we report twenty-one species of Odonata from the Bodoquena Mountains, Mato Grosso do Sul, Brazil. This species were collected during two systematic inventories carried out at six streams of the region, located at deciduous and semideciduous Atlantic forest. Novos registros de Odonata (Insecta) para Serra da Bodoquena, Mato Grosso do Sul, Brasil. Resumo. Neste estudo relatou-se 22 espécies de Odonata da Serra da Bodoquena, Mato Grosso do Sul, Brasil. Estas espécies foram coletados durante dois inventários sistemáticos realizados em seis córregos da região, localizado na porção Decídua e Semidecídua da Mata Atlantica.